Impact of diabetes and metformin use on recurrence and outcome in stage II–III colon cancer patients—A pooled analysis of three adjuvant trials. (May 2022) - Christou, Niki; Bergen, Elisabeth S.; Canton, Clemence; Le Malicot, Karine; Di Bartolomeo, Maria; Galli, Fabio; Galli, Francesca; Labianca, Roberto; Shi, Qian; Alberts, Steven R.; Goldberg, Richard M.; Lepage, Come; et al.
Abstract: Background: Diabetes mellitus (DM) has been associated with increased colorectal cancer (CRC) risk and worse prognosis in metastatic CRC patients. In this large, pooled analysis of non-metastatic colon cancer (CC) patients, we investigated the impact of DM and metformin treatment on recurrence and survival. Patients and methods: A patient-level pooled analysis from three randomised adjuvant trials was performed. All patients had resection with curative intent of stage II or III CC and were treated with standard adjuvant fluoropyrimidine and oxaliplatin (±cetuximab). We investigated the impact of DM and metformin treatment on time to recurrence (TTR) and overall survival (OS). Results: Of 5922 CC patients who had a median follow-up of 6.8 years, 621 patients (10.5%) had DM at CC diagnosis. Of those with DM, 327 patients (52.7%) were defined as metformin users and 294 patients (47.3%) as non-metformin users. CC patients with DM had a significantly shorter TTR (adjHR: 1.21; 95% CI, 1.03–1.42; p  = 0.017) and OS (adjHR: 1.29; 95% CI, 1.09–1.52; p  = 0.003) compared to non-diabetic CC patients. Diabetic CC patients not receiving metformin had a significantly worse TTR (adjHR: 1.28; 95% CI, 1.02–1.60; p  = 0.032) and OS (adjHR: 1.41; 95% CI, 1.13–1.77; p  = 0.003) as compared to non-diabetic patients. These worse outcomes were not significant in metformin users (TTR: adjHR: 1.16; 95% CI, 0.94–1.43; p  = 0.168; OS: adjHR: 1.19; 95% CI, 0.95–1.48, p  = 0.127). Conclusions: CC patients with DM had not only a significantly worse survival but also TTR. Furthermore, our data suggest that metformin may attenuate the detrimental effect of DM on CC patient outcomes. Highlights: DM was associated with impaired survival and time -to -recurrence in early CC patients. Both outcomes were the shortest in diabetic patients without metformin treatment. These findings seemed especially relevant in patients with KRAS and BRAF-wt tumours.